Environmental consulting fundamentals investigation and remediation - Alter, Benjamin (CRC Press, 2012)
"1 What Is Environmental Consulting? People, People who need people Are the luckiest people in the world --Bob Merrill and Jule Styne, "People" 1.1 The Environment and Environmental Hazards To understand what constitutes environmental consulting, we first must understand the meaning of "the environment." Webster's Dictionary defines environment as the complex of physical, chemical, and biotic factors (as climate, soil, and living things) that act upon an organism or an ecological community and ultimately determine its form and survival. Let's dissect this definition and discuss how it pertains to the contents of this book. As the definition indicates, physical factors include climate and soil, where climate includes the air, sunlight, and one of the fundamental requirements for life on earth (and a topic of discussion in many of the book's chapters), water. The chemical factors include the interactions between many of these physical factors as well as chemicals that occur naturally and those introduced by mankind. The "living things" indicated in the definition encompass the full range of living things: microbial, plant, and animal life. Conditions that have the ability to affect these living things are known as environmental hazards. An environmental hazard should not be confused with chemicals that can adversely change the environment. These chemicals, known in various contexts as pollutants or contaminants, are one of the three essential parts of an environmental hazard. For an environmental hazard to exist, three conditions must be present (see Figure 1.1). There must be a source of the pollution, a receptor for the pollution, and a pathway connecting the two. "-- Provided by publisher.
Keywords: Environmental impact analysis.; Environmental impact consultants.; elektronické knihy; electronic books